Penegakan Hukum terhadap Penyalahgunaan dan Pencegahan Pengguna Narkotika di Indonesia - Damar Bastiar (JURNAL RECHTENS, 2019)
Drug abuse is still a chronic problem that befell Indonesia, cases of methamphetamine circulation and many international drug dealers have been caught in recent years to prove that Indonesia is in a state of drug emergency. Drug trafficking carried out with sophisticated techniques has penetrated throughout Indonesia. It can be said that there has been a change in the mode of syndicates, where specific types of psychotropic substances are no longer imported, but their distributors prefer to make factories to produce their own. Procurement of raw materials,compounding, until the recruitment of people related to the division of labor in producing drugs is really well planned. This can be said when looking at trends in cases of narcotics factories that continue to emerge. Narcotics crime has been transnational in nature which is carried out using high modus operandi, sophisticated technology, supported by a broad network of organizations, and has caused many victims especially among the younger generation who are very detrimental to the lives of people, the nation, and the state of crime.Keywords: drugs, people, crime